The measurement of consumer green purchase intention determinants toward hybrid cars in Malaysia - Meor Ahmad, Siti Salwani; Ali, Noor Azman (Innovare Academic Sciences, 2021)
Transportation is acknowledged as one of the major sources of greenhouse gasses and air pollution. Thus, promoting cars with high efficiency in fuel consumption and reduce emission is required to replace conventional cars. In that case, encouraging consumer to purchase green car by identifying factors that affect green car purchase intention among Malaysian is important. This study provides some preliminary evidence on determinants of hybrid cars purchase intention in Malaysia and green product attachment as a mediator. Hence, the validity and reliability of instrument were examined via pretest and a pilot test. The data normality also was checked by using SPSS version 21. The findings suggest that the Green Trust and Green Product Attachment are the most significant factors on the influence toward Green Purchase Intention of hybrid cars in terms of reliability score.